PENGARUH MEDIA PEMBELAJARAN PAPAN PERKALIAN TERHADAP PEMAHAMAN DAN KEMANDIRIAN SISWA KELAS IV B PADA MATA PELAJARAN MATEMATIKA DI UPTD SDN SEPULUH 01 - Iffatus Sofak; Yunita Hariyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to determine the effect of multiplication board learning media on the understanding and independence of Grade IV B students in mathematics at UPTD SDN Sepuluh 01. The type of research used is quantitative research with a one-group pretest–posttest design method. The population in this study consisted of all Grade IV B students with a total sample of 30 students.The instruments used in this study included a test instrument in the form of questions to measure students’ learning understanding, while the non-test instrument was a questionnaire to measure students’ independence. To determine whether the instruments were appropriate to use, validity and reliability tests were conducted. Meanwhile, to test the hypothesis, normality testing and paired sample t-test were used.By using the SPSS application, the results showed a significance value of 0.000 < 0.05, indicating that there is an effect of the multiplication board learning media on students’ learning understanding. In addition, the second test output also showed a significance value of 0.000 < 0.05, indicating that there is an effect of the multiplication board learning media on students’ independence.Therefore, it can be concluded that the multiplication board learning media has an effect on the understanding and independence of Grade IV B students in mathematics at UPTD SDN Sepuluh 01.